2013
DOI: 10.4141/cjps2013-061
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation in dry edible beans with various herbicides

Abstract: Soltani, N., Blackshaw, R. E., Gulden, R.H., Gillard, C. L., Shropshire, C. and Sikkema, P. H. 2013. Desiccation in dry edible beans with various herbicides. Can. J. Plant Sci. 93: 871–877. There is little information available on the effect of diquat, carfentrazone-ethyl, glufosinate ammonium, flumioxazin and saflufenacil applied alone or in tankmix combination with glyphosate as harvest aids in dry bean production under environmental conditions of the various production regions in Canada. A total of 11 field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
(19 reference statements)
1
26
0
3
Order By: Relevance
“…Although tankmix combinations of glyphosate and diquat, glufosinate, flumioxazin, or saflufenacil improved desiccation speed compared with glyphosate alone, the converse was not true; addition of glyphosate did not improve the desiccation efficacy of diquat, glufosinate, flumioxazin, or saflufenacil. This finding is similar to those of Soltani et al (2013) who noted that the addition of diquat, glufosinate, carfentrazone, flumioxazin, or saflufenacil to glyphosate improved the degree of crop desiccation and late-season weed control compared with treatments where only glyphosate was applied. Desiccation of all plant parts by the recently registered harvest aids, flumioxazin and saflufenacil, was equal to or better than previously relied on desiccants such as glyphosate, diquat, and carfentrazone.…”
Section: Desiccationsupporting
confidence: 88%
“…Although tankmix combinations of glyphosate and diquat, glufosinate, flumioxazin, or saflufenacil improved desiccation speed compared with glyphosate alone, the converse was not true; addition of glyphosate did not improve the desiccation efficacy of diquat, glufosinate, flumioxazin, or saflufenacil. This finding is similar to those of Soltani et al (2013) who noted that the addition of diquat, glufosinate, carfentrazone, flumioxazin, or saflufenacil to glyphosate improved the degree of crop desiccation and late-season weed control compared with treatments where only glyphosate was applied. Desiccation of all plant parts by the recently registered harvest aids, flumioxazin and saflufenacil, was equal to or better than previously relied on desiccants such as glyphosate, diquat, and carfentrazone.…”
Section: Desiccationsupporting
confidence: 88%
“…Previous research on harvest aids reported that the application of glyphosate at five rates, from 0.56 to 3.36 kg, 3 weeks before soybean harvest, resulted in decreased soybean yield [ 9 ], and application before physiological maturity resulted in decreased seed weight, emergence, and vigor [ 10 , 11 ]. It was also reported that the intent of pre-harvest, crop harvest aid application was to rapidly dry vegetative and reproductive plant tissues, including seeds, without affecting seed yield and seed quality [ 12 , 13 , 14 ]. It was reported that the application of glyphosate at 1%, 10%, or 100% of an 890 g ai ha -1 rate to soybean near seed maturity had significant effects on germination and/or growth of the resulting F1 generation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It moves both acropetally and basipetally in plants and affects symptoms similar to other contact herbicides (Soltani et al, 2010 ). Glufosinate can translocate within plants, but has rapid phytotoxicity that limits its mobility (Grossmann et al, 2010 ; Soltani et al, 2013 ). Pyraflufen-ethyl and flumioxazin are also potential harvest aids for lentil crops in Western Canada (Risula, 2014 ; Zhang et al, 2016 ) and are commonly used as desiccants in cotton (Griffin et al, 2010 ) and common bean (Soltani et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glufosinate can translocate within plants, but has rapid phytotoxicity that limits its mobility (Grossmann et al, 2010 ; Soltani et al, 2013 ). Pyraflufen-ethyl and flumioxazin are also potential harvest aids for lentil crops in Western Canada (Risula, 2014 ; Zhang et al, 2016 ) and are commonly used as desiccants in cotton (Griffin et al, 2010 ) and common bean (Soltani et al, 2013 ). Overall, minimal research has been conducted to assess the impact of the complete spectrum of harvest aids (e.g., diquat, pyraflufen, glufosinate ammonium, flumioxazin, and saflufenacil) alone or in combination with glyphosate with respect to their effects on seed biology and post-harvest processing of lentil.…”
Section: Introductionmentioning
confidence: 99%